2
$\begingroup$

The title says it all. Why does $(-2^2)^3$ equal $-64$ and not $64$? This was on my algebra final, and I am completely stuck on how it works.

$\endgroup$
  • 1
    $\begingroup$ I always have an issue with this because it is somewhat of an ambiguous notation. I think that when doing mathematics, that the concepts should be tested and not the differing interpretations of a problem. $\endgroup$ – yousuf soliman Jun 19 '13 at 19:22
4
$\begingroup$

The negative sign ($-$) applies to the quantity $2^2$, so that $-2^2$ means $-(2^2)=-4$, not $(-2)^2=4$. $$(-2^2)^3=(-4)^3=-64$$

$\endgroup$
  • 2
    $\begingroup$ So for it to actually be 64, would the problem need parentheses around the -2? So would it have to be $((-2)^2)^3$ for it to equal 64? $\endgroup$ – S17514 Jun 19 '13 at 19:19
  • $\begingroup$ Yup, that's right. $\endgroup$ – Zev Chonoles Jun 19 '13 at 19:20
1
$\begingroup$

Note that $-2^2 = - (2 \times 2) = -4$ and is not $(-2) \times (-2) = 4$. Hence, $$(-2^2)^3 = (-4)^3 = (-4) \times (-4) \times (-4) = - 64$$

In general, when $m$ is a positive integer, we have $$-a^m = - (\underbrace{a \times a \times \cdots \times a}_{m \text{times}})$$ and is not $$(-a)^m = (\underbrace{(-a) \times (-a) \times \cdots \times (-a)}_{m \text{times}})$$

$\endgroup$
  • 1
    $\begingroup$ It's worth noting that some simplistic tokenizers do parse $-2^2$ as $(-2)^2$, which is non-standard. I believe most spreadsheets are guilty of this (perhaps to stay compatible with Microsoft Excel). $\endgroup$ – Erick Wong Jun 19 '13 at 19:21
0
$\begingroup$

Rewrite it as

$(-4)^3=(-1)^3 \cdot 4^3=-64$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.